(untitled) (Journal of Parents and Teachers, 2014)
Any educational situation must take into account the context, especially in extreme situations such as war, hunger, marginalization or political coercion. In these situations, the teacher’s commitment to the transformation of their environment is a reality. There are several situations that make it difficult for teachers to teach and work in educating values, especially when dealing with poverty and refugees. Above all, it explains the importance of children’s daily attendance at school.